Design of an Integrated Health Monitoring System on an IoT-Based Framework - Anshim Verma; Kamlesh Kumar Singh (International Journal of Biomedical Innovations and Engineering, 2026)
With the advent of industrialization, health ailments have become a major cause of concern owing to an inactive and fast lifestyle, polluted environments, and detrimental eating habits. However, IoT has become a boon for the health sector and humanity on account of its countless benefits, rendering improved quality of service and patient-centric care. An Integrated Health Monitoring System (IHMS) is presented in this paper. This new IoT-based framework integrates wearable technology with sensors and secure cloud analytics to address the current challenges and improve the quality of service. This paper further investigates the significant applications of the Internet of Things (IoT) in the healthcare sector, particularly focusing on areas, such as remote patient monitoring, intelligent medical devices, and hospital resource optimization. It highlights how IoT technologies enable continuous health data collection, real-time monitoring, and improved communication between patients and healthcare providers. In addition, the study presents a detailed analysis of the Intelligent Healthcare Monitoring System (IHMS) model, including its structural framework, operational mechanisms, and technological components. The paper also explores the potential to transform and enhance existing healthcare standards by improving the efficiency, accuracy, and accessibility of medical services.
Keywords: Healthcare; Internet of Things; IoT applications; Wearable devices; data privacy; integrated health monitoring system; remote monitoring